Pelatihan Pembinaan UMKM Berbasis Teknologi untuk Meningkatkan SDM Pelaku Usaha Ayam Balung Empuken - Citra Anisa Tika Putri; Annisa Maulana Majid; Dwi Astuti; Fahrurozi Muarief (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2025)
As the backbone of the global economy, Micro, Small, and Medium Enterprises (MSMEs) have a very important role. One of the success factors for SMEs is the effective management of Human Resources (HR). HR management is not only about recruiting and retaining employees, but it also involves strategies that blend human potential with business goals. Additionally, managing an employee team can be a challenge that requires the right skills and strategies. From sourcing top talent to designing effective training programs, everything needs to be well organized to support business growth and sustainability. The Community Service Activity of the Faculty of Economics and Business, Universitas Pelita Bangsa will be carried out online and offline (hybrid), located at the Alam Raya Residence Cluster Block B2 No 12A, Sukasari, Serang Baru, Bekasi Regency and also via Zoom.